ANALISIS IMPLEMENTASI PRINSIP EKONOMI SYAIRAH PADA CV. BERSATU JAYA - M Heru Sunardi; Achmad Sjamsudin (ICO EDUSHA, 2021)
This research aims to find out the implementation of sharia economic principles in CV. Bersatu Jaya Sidoarjo Regency. The method of data analysis used in research is qualitative analysis with normative and sociological approaches. Research data is obtained from primary data and secondary data with data collection techniques in the form of observations, documentation, interviews. The results of this study show that CV. Bersatu Jaya has applied sharia economic principles in its company's operations. This is because in the company's operational activities contain Islamic economic value such as Tawhid, Justice, and Leadership. Keywords: Implementasi, Nilai Ekonomi Syariah, Sidoarjo References Khodijah Ishak, “Maqosid Syari’ah Sebagai Dasar Sistem Ekonomi Berkeadilan”, Hal. 597. Umer Chapra, Masa Depan Ilmu Ekonomi, (terj.) Ikhwan Abidin, (2001). The Future of Economics: An Islamic Perspective, Jakarta: Gema Insani Press, hlm. 202-206. Martina Khusnul Khotimah. (2019) “Implementasi Prinsip Produksi Ekonomi Islam Pada Mebel Ira Bersaudara Kota Bengkulu”, AL-INTAJ, Vol.5, No.1 Muh. Ihsan, Wahidah Abdullah, Bahrul Ulum Rusydi. (2018) “Implementasi Prinsip Ekonomi Islam Oleh Pedagang Dalam Melakukan Penimbangan Sembako Di Pasar Soppeng”, An-Nisbah: Jurnal Ekonomi Syariah Vol. 05, No.01 Viva Budy, “Sebanyak 86,88% Penduduk Indonesia Beragama Islam”, https://databoks.katadata.co.id/datapublish/2021/09/30/sebanyak-8688-penduduk-indonesia-beragama- islam, (di akses pada 24 November 2021, pukul 05.10)